Marine Pollution Response in Northeast Asia and the NOWPAP Regime - Kim, Suk Kyoon (Ocean development and international law, 2015)
The seas of Northeast Asia are subject to significant risk from oil and hazardous and noxious substances spills. This article examines the issues concerning marine pollution incidents in the context of the Action Plan for the Protection, Management and Development of the Marine and Coastal Environment of the Northwest Pacific Region (NOWPAP) regime. It also discusses the institutions and legal instruments that deal with marine pollution response in the NOWPAP region.